PHYSICAL CHEMICAL COMPOSITION AND PROXIMAL ANALYSIS OF THE FRUIT OF SOFAIQUE Geoffroea decorticans (Hook. et Arn.) FROM THE ICA-PERU REGION - Pillco Cochan, Carlos J. (2021)
The current study evaluated Geoffroea decorticans (Hook. et Arn.) fruit, from the coastal desert in the department of Ica (Perú), well known by the name of "Sofaique" and in other regions "Chañar". The main objective of this research was to obtain data about its physicochemical and nutritional composition; the sample was extracted of fruit and was separated into three parts: epicarp, mesocarp and pit. The AOAC methodology was applied in order to determine its chemical and nutritional properties using only the mesocarp with samples of 3 grams each. For the physical characterization, the fruit dimensions were measured in its three axes (polar, equatorial and caliber) with a digital caliper and the weight by an analytical weighting scale. The average results of the whole dimensions of fruit were: equatorial axis 22,32 mm, polar axis 21,69 mm and caliber 19,60 mm; the average of the fruit proportions were: pulp 38,51 %, stone 32,91 % and peel 28,58 %, and the average weight of the whole fruit was 3,88 g; the main results of the proximal analysis and chemical composition for mesocarp (pulp) were 9,17 % protein; 2,59 % ashes; 20,20 % moisture content; 1,38 % lipids; 66,66 % carbohydrates; PH 5,2; 0,05 % titratable acidity and 4,0° Brix in soluble solids. The results indicate that “sofaique” turns out to be a nutritious and palatable fruit, considering that it is a species that grows in semi-arid and arid areas with limited nutrients available in soil.